Problems Of Meaning and Content in Psycholinguistics - Yusuf Beknazarovich Boboyev (Genius Journals, 2022)
The article talks about word meaning and language meaning in psycholinguistics, their meaningful connection and problems
Keywords: psycholinguistics; meaning; aspect; component